A prediction model for viability at the end of the first trimester after a single early pregnancy evaluation. (14th February 2013) - Oates, Jennifer; Casikar, Ishwari; Campain, Anna; Müller, Samuel; Yang, Jean; Reid, Shannon; Condous, George
<x xml:space="preserve">Abstract</x> Objective The aim was to develop a new model to predict the outcome at the end of the 1st trimester after a single visit to the early pregnancy unit (EPU). Methods Prospective observational study in the EPU at Nepean Hospital, between November 2006 and February 2009. Data were collected from all women in the 1st trimester of their pregnancy who had a live intrauterine pregnancy (IUP) at the 1st transvaginal ultrasound scan (TVS). 29 historical, clinical and ultrasound end points were recorded. Women were followed until the final diagnosis was established at the end of the 1st trimester: viability or nonviability. A multinomial logistic regression model was developed. The performance of this model was evaluated using receiver operating characteristic (ROC) curves. Results Data from 416 pregnancies were included: 92.1% were live beyond the 1st trimester, and 7.9% had miscarried. The most useful prognostic variables for developing the logistic regression model were gestational age by dates, vaginal (PV) bleeding, PV clots, gestational age by TVS, consistency with menstrual dates, mean gestational sac (GS) size, mean yolk sac (YS) size and number of previous caesarean sections. Used retrospectively on 416 women based on 25 imputations, the model gave an AUC of 0.88. Based on cross‐validation, the independent predictive power obtained an AUC of 0.78. Conclusions We have developed a new model to predict the outcome of the 1st trimester in women with live IUP at the 1st scan.